2013
DOI: 10.1175/jamc-d-12-0328.1
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Cloud Properties Using CALIPSO Imaging Infrared Radiometer. Part II: Effective Diameter and Ice Water Path

Abstract: This paper describes the version-3 level-2 operational analysis of the Imaging Infrared Radiometer (IIR) data collected in the framework of the Cloud–Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) mission to retrieve cirrus cloud effective diameter and ice water path in synergy with the Cloud–Aerosol Lidar with Orthogonal Polarization (CALIOP) collocated observations. The analysis uses a multisensor split-window technique relying on the concept of microphysical index applied to the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
71
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 37 publications
3
71
0
Order By: Relevance
“…Another estimate of r ei is derived from a combination of the CloudAerosol Lidar with Orthogonal Polarization (CALIOP) and the Imaging Infrared Radiometer (IIR) instruments (Garnier et al, 2013) on the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellite (Winker et al, 2010). Additional active-passive algorithms are also available.…”
Section: Introductionmentioning
confidence: 99%
“…Another estimate of r ei is derived from a combination of the CloudAerosol Lidar with Orthogonal Polarization (CALIOP) and the Imaging Infrared Radiometer (IIR) instruments (Garnier et al, 2013) on the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellite (Winker et al, 2010). Additional active-passive algorithms are also available.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies (Cooper et al, 2007;Cooper and Garrett, 2010;Wang et al, 2011) have shown that cirrus optical properties may be retrieved with a better accuracy using a combination of TIR channels instead of visible and near-infrared (VNIR) channels (such as the Nakajima and King method, Nakajima and King, 1990), as long as the cirrus is optically thin enough (with a visible optical thickness between roughly 0.5 and 3) and the CED is smaller than 40 µm. For example the split-window technique (Inoue, 1985) applied to the Advanced Very-High-Resolution Radiometer (AVHRR; Parol et al, 1991) and the Imaging Infrared Radiometer (IIR) onboard CALIPSO (Garnier et al, 2012(Garnier et al, , 2013) is used to retrieve CED and COT from the brightness temperature difference of two different channels in the infrared atmospheric windows where gaseous absorption is small. Based on the same spectral information, an optimal estimation method (OEM; Rodgers, 2000) is used for the Atmospheric Infrared Sounder V6 (AIRS, Kahn et al, 2014Kahn et al, , 2015) and in the research-level code of Wang et al (2016b, a) for MODIS.…”
Section: Introductionmentioning
confidence: 99%
“…Global satellite observations are well suited to monitoring and investigating cloud evolution and characteristicsm because passive top-of-atmosphere (TOA) radiometric measurements allow for retrievals of cloud properties such as optical thickness and ice crystal effective diameter. In this work, we focus on infrared measurements obtained by the Imaging Infrared Radiometer (IIR; Garnier et al, 2012Garnier et al, , 2013 onboard the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO).…”
Section: Introductionmentioning
confidence: 99%